Development of a Vertical Garden Project Learning Video to Enhance Children's Naturalistic Intelligence in Kindergarten - Asni Susanti; Yaswinda; Dadan Suryana; Nurhafizah (Jurnal Pendidikan Anak Usia Dini Undiksha, 2026)
Limited learning media that can stimulate naturalistic intelligence in early childhood, particularly through direct nature-based learning experiences in space-constrained environments, poses a challenge in creating meaningful and contextual learning processes. This study aims to develop and evaluate the effectiveness of video-based learning media with the concept of a vertical garden to enhance the naturalistic intelligence of children aged 5–6 years. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The subjects of the study were one teacher and 17 children aged 5–6 years. Data collection techniques included expert validation, observation, teacher questionnaires, and child assessment sheets. The research instruments consisted of validation sheets, practicality questionnaires, and effectiveness assessment sheets. Data were analyzed using descriptive quantitative techniques by calculating percentage scores for each assessment aspect. The results showed that the developed video media achieved a very high validity score of 90.3%, a practicality level of 93.75%, and an effectiveness score of 90.1% in improving children’s naturalistic intelligence. Therefore, the developed learning media is considered feasible, practical, and effective for use in early childhood education. This study implies that video-based learning media with a contextual approach can serve as an innovative alternative to optimize the stimulation of children’s naturalistic intelligence, particularly in learning environments that are limited in space and access to direct natural settings.